Penerapan Ornamen Sebagai Ciri Budaya Tionghoa pada Chinese Restaurant di Jakarta - Polniwati Salim (Bina Nusantara University, 2015)
Chinese restaurants are obviously connected to Chinese culture for it holds a great importance and is even the core point of creating art. The art would be based upon the aesthetic contents which contain symbolic meaning in Chinese philosophy. In a typical chinese restaurant the connection between tradition and art is represented in the form of ornaments that acts functionally and has specific unique characteristics. This study was conducted by qualitative method with survey, interview, and documentation of the ornaments in chinese restaurant. This study aims to introduce and enrich the knowledge, as the ornaments stand for showing the identity of chinese culture in chinese restaurant. The aesthetical theory about the art of design and the implementation of chinese ornaments took part in the study as well. Result of the study shows that the chinese restaurant observed has implemented the interior and applied the ornaments well in showing chinese identity. Besides, the materials used for furniture and interior elements have given the nuances of Chinese culture. Study concludes that the aesthetic atmosphere of the interior of Dian Xiao Er Restaurant is calm, peaceful, and relaxing like sitting in a modest diner. The dynamics that was created is something impressed repetitive yet not boring